Associations between the codon 72 polymorphism of the TP53 gene and the risk of recurrent implantation failure†. Issue 2 (10th November 2015) - Feng, Yi; Wu, Yuan‐Yuan; Lin, Xiao‐Juan; Yang, Lu; Luo, Zhi‐Juan; Zhou, Ying‐Hui; Chen, Jing; Li, Ning; Lin, Zhong; Zhao, Xia
Abstract: Aim: Recurrent implantation failure (RIF) is the most common cause of unsuccessful pregnancy after assisted reproductive techniques. The tumor protein P53 (TP53) codon 72 polymorphism (G‐C transversion) has been explored in susceptibility to RIF, but inconclusive results have been reported. The aim of this article is to estimate the associations between the TP53 codon 72 polymorphism and the risk of RIF. Materials and Methods: A comprehensive search for relevant articles was conducted. The odds ratios (ORs) and 95% confidence intervals (CIs) for CC + GC versus GG, CC versus GC + GG, CC versus GG, GC versus GG genotypes, and C versus G allele, were estimated. Publication bias was explored. Statistical analyses were performed using RevMan 5.2 and Stata 11.0 software. Results: A total of five case‐control studies in five articles with 417 RIF cases and 325 controls were included. An overall random effect OR of 1.20 (95% CI, 0.66–2.19; P = 0.55) in the dominant model (CC + GC vs GG) was found. The results suggested that a lack of increased or decreased risks were found in individuals who carried the CC homozygote and heterozygote GC, in comparison with the homozygote GG. However, in subgroup analysis by ethnicity, a significantly increased risk was observed among Latin Americans in the dominant model (OR, 1.56; 95% CI, 1.04–2.33; P = 0.03). Conclusions: This meta‐analysis shows that the TP53 codon 72 polymorphism is not associated with RIF risk in the overall population; however, associations were found in the Latin American population.